The Intellectualization of Chicago&s Culture: An Ethnographic Analysis of the Chicago Cultural Center. Issue 1 (1st December 2020) - Walters, Noah
Abstract: The Chicago Cultural Center (CCC), centrally-located on Randolph and Michigan, aims to represent the diverse population of Chicago. Each year, the Center draws thousands of tourists and locals, eager to see the famous Preston Bradley Tiffany Dome or one of the many constantly-rotating exhibits provided by the Chicago Architectural Foundation. Functionally, the Center is open every day with long hours and free admission, seemingly enticing all to enter. Rather contrary to the ethnic diversity of Chicago, however, the CCC, although it is staffed by a wide range of minorities, caters mostly to upper-middle class whites. This ethnographic analysis utilizes interviews and anthropological tourism literature to explain the intellectualization of this Chicago landmark.